THU0594 CLINICAL VERSUS IMAGING REMISSION IN JUVENILE IDIOPATHIC ARTHRITIS (JIA): PRELIMINARY RESULTS OF THE REMECO STUDY. (June 2019) - Mazzoni, Marta; Merlo, Silvia; Pistorio, Angela; Viola, Stefania; Consolaro, Alessandro; Ravelli, Angelo; Malattia, Clara
Abstract : Background: remission is becoming a realistic target in JIA, but clinical remission (CR) may not accurately reflect real absence of synovitis. It would be desirable to have instruments to predict the risk of relapse in patients in CR in order to establish the most appropriate therapeutic strategy. Despite in RA the role of imaging to predict disease flare is established, this field has remained almost unexplored in JIA. Objectives: 1) to investigate the prevalence of musculoskeletal ultrasound (MSUS)-detected subclinical synovitis in JIA patients in CR; 2) to establish which and how many joints should be scanned to reliably assess remission; 3) to evaluate the persistence of subclinical synovitis over the time; 4) to investigate whether subclinical synovitis entails a risk of disease flare; 5) MSUS data will be integrated with serum levels of inflammatory biomarkers to develop a multidimensional measure of remission. Methods: it is a longitudinal prospective 4 years study started on November 2017. So far we have enrolled 99 consecutive JIA patients who met the Wallace criteria for CR. For each patient 46 joints were scanned for synovial hyperplasia/joint effusion and PD signal, all graded semiquantitatively on a 0–3 scale independently by 2 expert ultrasonographers. Subclinical synovitis was defined when total synovitis score for each joint was ≥2. MSUS was performed at baseline and at 6 month follow up visit. At inclusion serum assays have been stored to determine levels of inflammatory biomarkers (S100A8/9-A12, bFGF, IL-6, IL-10, CXCL9-10, VEGF, YKL40). A flare of synovitis was defined as a recurrence of clinically active arthritis. Results: 99 patients (79.8% F; median age 11.3 y; median disease duration 5.3 y; median CR duration 1.6 y) were included. Thirty-eight/99 (38.4%) patients had persistent oligoarthiritis; 34/99 (34.3%) extended oligoarthiritis; 22/99 (22.2%) polyarthiritis; 5/99 (5.1%) systemic arthritis. Fifty-nine/99 (59.6%) patients were in CR on medication. Subclinical synovitis was detected in 54/99 (54.5%; 95% CI: 45.2 – 65.5%) patients, PD in 18/99 (18.2%; 95% CI: 11.1 – 27.2%) patients; subclinical tenosynovitis in 7/99 (7.1%; 95% CI: 2.9 – 14%) patients. Subclinical synovitis was found more frequently in the ankle [31/54 (57.4%) patients] and wrist joints [17/54 (31.5%) patients]. No patients had subclinical synovitis in the hip. A 14-joint reduced count including bilateral knee, ankle (tibiotalar, subtalar and talonavicular joints), wrist (radiocarpal and intercarpal joints) and elbow joints, detected 92.6% of children with subclinical synovitis. Twenty-five/99 (25.2%) patients in persistent CR were reassessed with MSUS at a follow up visit (median follow up duration 7 months): 82.3% of patients showed persistent subclinical synovitis. Sixty-four/99 (64.6%) patients had a clinically follow up of at least 6 months and 9/64 (14%) patients experienced a disease flare (median time to flare 6.6 months). Six/9 (66.7%) patients who experienced a relapse had subclinical synovitis at baseline. Conclusion: our preliminary results confirm the discrepancy between clinical and imaging remission and that clinical evaluation may not sensitive to detect an inflammation-free state. Bilateral US assessment of the elbow, wrist, knee and ankle joints is reliable to detect subclinical synovitis. So far, patients who have relapsed are a small percentage, but to extend follow up is crucial to test predictive value of MSUS. Imaging findings will be combined with serum biomarkers leading to the construction of a predictive model. References: [1] De Lucia O, et al. Baseline ultrasound examination as possible predictor of relapse in patients affected by juvenile idiopathic arthritis (JIA). Ann Rheum Dis. 2018Oct;77(10):1426-1431. Disclosure of Interests: Marta Mazzoni: None declared, Silvia Merlo: None declared, Angela Pistorio: None declared, Stefania Viola: None declared, Alessandro Consolaro Grant/research support from: AbbVie, Pfizer, Angelo Ravelli Grant/research support from: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Consultant for: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Speakers bureau: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Clara Malattia: None declared